Aransemen Lagu Buku Ende No. 741 “Nang Ro Pe Haba-haba I” Menggunakan Aplikasi Sibelius dalam Iringan Ibadah di Gereja HKBP Siabal abal Resort Sipahutar - Epsan Harianja; Monang Asi Sianturi; Roy J. M. Hutagalung (Coram Mundo: Jurnal Teologi dan Pendidikan Agama Kristen, 2024)
The aim of this research is to find out how the song "Nang Ro Pe Haba-haba I" is arranged using the concept of using the Sibelius application and to increase the insight of the writer and especially church musicians who are learning to deepen the principles of arrangement. Arrangement is the activity of rewriting an existing piece of music or work to use an instrument or voice in harmony or addition to the original work, which is made to beautify the work. Currently, musicians, including church musicians, also arrange current church songs. The young musicians dared to create something new in their musical performance by arranging the church song by adding a variety of creative accompaniments. This arrangement refers to a church music arrangement taken from the song Buku Ende HKBP No. 741 “Nang Ro Pe Haba-haba I”. This song is played with a Moderato tempo or around 104 BPM. This song was created by Vernon J. Charlesworth with the title The Lord's Our Rock, in Him we hide which was later translated into Indonesian Batak by Bonaria Hutabarat. Meanwhile, the form of arrangement presented leads to mixed ensemble music playing using the music application, namely Sibelius. The Sibelius application is a music application that is used to create song scores, arrange songs and there are several other features to make it easier for musicians to express their works. In this research, the author used the Sibelius application to arrange church songs to accompany worship. This research was conducted at the HKBP Siabal Abal Ressort Sipahutar church with the aim of motivating the church music players to be more enthusiastic in accompanying worship at the church. The author presents the results of the arrangement using audio-visual media.